2011
DOI: 10.1016/j.foodchem.2010.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Leu and Hyp residues to antioxidant and ACE-inhibitory activities of peptide sequences isolated from squid gelatin hydrolysate

Abstract: ** This centre has implemented and maintains a Quality Management System which fulfils the requirements of the ISO standard 9001:2000 AbstractSquid gelatin obtained from inner and outer tunics was hydrolyzed with Alcalase to isolate antioxidant peptide sequences. The ACE-inhibitory activity of the isolated peptides was also evaluated. After fractionation by ultrafiltration and size-exclusion chromatography into four fractions, the antioxidant activity of the peptide fractions was determined by radical scavengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
161
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(179 citation statements)
references
References 50 publications
10
161
1
7
Order By: Relevance
“…This balance was showed in this peptide, the hydrophilic amino acids were 7/15 and the hydrophilic amino acids were 5/15. The sidechain of Gly consists of a single hydrogen atom and may confer high flexibility of the peptide to capture radicals, which was also suggested by Alemán et al [28]. In addition, it was reported that bioactive peptides usually contain 2-20 amino acid residues per molecule, and the lower the molecular weight, the higher their chance to cross the intestinal barrier and exert biological effects [40,41], and the peptide in this study was composed of 15 amino acid residues.…”
Section: Characterization Of Purified Antioxidant Peptidessupporting
confidence: 66%
See 1 more Smart Citation
“…This balance was showed in this peptide, the hydrophilic amino acids were 7/15 and the hydrophilic amino acids were 5/15. The sidechain of Gly consists of a single hydrogen atom and may confer high flexibility of the peptide to capture radicals, which was also suggested by Alemán et al [28]. In addition, it was reported that bioactive peptides usually contain 2-20 amino acid residues per molecule, and the lower the molecular weight, the higher their chance to cross the intestinal barrier and exert biological effects [40,41], and the peptide in this study was composed of 15 amino acid residues.…”
Section: Characterization Of Purified Antioxidant Peptidessupporting
confidence: 66%
“…Generally, aromatic amino acids in peptide sequences can donate protons easily to electron-decent radicals, so they are believed to be effective radical scavengers [27]. However, the amino acid compositions from collagen to gelatin hydrolysates are rich in residues of Gly, Ala, Pro, Hyp, Glx and Asx, but poor in Met, Cys, His and Tyr [28][29][30]. Many peptides from collagen hydrolysis have been described to have antioxidant capacity without containing any of the above-mentioned proton-donating amino acid residues in their sequences [24,31].…”
Section: Characterization Of Purified Antioxidant Peptidesmentioning
confidence: 99%
“…In fact, several studies have reported that compounds with biological and functional properties are found at high concentration in squid discard, having potential applications in the medical, food, mixed-feed, microbiological, and other industries (Alemán, Giménez, Pérez-Santin, Gómez-Guillén & Montero, 2011;Nakchum & Kim, 2015;Ramasamy, Subhapradha, Shanmugam, & Shanmugam, 2014). The main byproduct from jumbo squid is the skin, and it is the most studied.…”
Section: Introductionmentioning
confidence: 99%
“…Several natural ACE inhibitory peptides have been isolated from collagen and gelatin enzymatic hydrolysate of various food protein sources such as porcine skin collagen (Ichimura et al 2009), bovine skin gelatin , fish skins Nagai et al 2006;Park et al 2009), fish cartilage (Nagai et al 2006), scales (Fahmi et al 2004), squid (Alemán et al 2011) and sea cucumbers protein hydrolysates (Zhao et al 2007) as an alternative approach to the synthetic ACE inhibitory drugs.…”
Section: Introductionmentioning
confidence: 99%